Interpersonal Meaning and Linguistic Politeness in Eschatological Hadith Based on Systemic Functional Linguistics - Ali Idris, Ilham Maulana; Adam, Mansour Gadalla Adoum; Al Farisi, Mohamad Zaka (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study aims to identify interpersonal meaning and linguistic politeness principles embedded in eschatological hadiths and to interpret the relationship between interpersonal meaning and politeness as a representation of Islamic values of da‘wah, communicative ethics, and moral guidance within eschatological discourse. Employing a descriptive qualitative method grounded in Systemic Functional Linguistics (SFL), the study analyzes five selected hadiths collected through documentation and categorized based on their dialogic strategies. The analysis demonstrates that the Prophet Muhammad SAW consistently conveyed eschatological messages through linguistic structures that uphold politeness principles aligned with Leech’s maxims of Tact, Approbation, and sympathy, ensuring that admonitory and doctrinal messages were delivered with gentleness, empathy, and guidance-oriented communication. Furthermore, the findings reveal a clear distinction in the Prophet’s interpersonal speech patterns: interactions with his wives are characterized by intimate, personal, and emotionally nuanced expressions marked by moderate modality and soothing lexical choices, whereas his speech to the Companions tends to be more formal, instructive, and authoritative, employing more potent modality to reflect his pedagogical role and public leadership.